Preterm birth and its outcome - Radhanpuri, Farhin; Desai, Deepak A. A.; Sharma, Jyoti; Kaur, Pawanpreet (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Background: Preterm birth is a major challenge in perinatal health care. Most perinatal deaths occur in preterm infants, and preterm birth is an important risk factor for neurological impairment and disability. Preterm birth not only affects infants and their families-providing care for preterm infants, who may spend several months in hospital, has increasing cost implications for health services. This study aims at to study the causes of preterm birth, perinatal outcome, identify the cases which need intervention. Methods: This is a retrospective study done at the Department of Obstetrics and Gynecology, Dhiraj General Hospital from May 2012 to May 2013. Total 272 preterm deliveries were enrolled for the study. Results: According to our study, preterm birth percentages 51% in low socio economic status, 58% in severe anaemia, 55% in unregistered, 37% in h/o previous preterm birth, 41% b/w 28-32 wks of gestational age, 46% b/w 32-36 wks of gestational age. Conclusions: In our population preterm birth is more common in poor socio economic status, women with anaemia, malnutrition and these factors can be eliminated by proper nutrition and health education by health workers.